(untitled) (LACCEI, 2024)
The objective of this thesis was to determine the generation, disposal and impact of facemasks used during the Covid-19 pandemic in Lima in 2022. A descriptive research was carried out, whose approach corresponds to a quantitative study, with a non-experimental cross-sectional design. The population and sample corresponds to the inhabitants of the department of Lima, with a finite population of 380 inhabitants. A virtual survey was used as a technique this instrument was validated by 3 experts with experience in solid waste management. The results show that the most commonly used type of mask generation was KN95, with the place of greatest use being public transportation and the time of use being 3 to 4 hours per day. The population indicates that they use approximately 11 to 20 masks per month according to the respondents, they dispose of them in the containers at home. It can be concluded that the population of the department of Lima does not adequately segregate masks and, consequently, the impact of masks can be seen on beaches, rivers, public roads and animals according to those surveyed, the animals most affected are aquatic animals.